Mozambique - Country Economic Memorandum : Reigniting Growth for All - World Bank (Washington, DC, 2022)
Mozambique has experienced rapid growth for over two decades. Growth accelerated remarkably following the end of the civil war, averaging 7.9 percent over 1993-2015, among the highest in sub-Saharan Africa (SSA). However, growth decelerated sharply following the hidden debt crisis in 2016, which led to a crisis of economic governance and a protracted economic slowdown, with growth falling to 3 percent in 2016-2019. The growth slowdown has been further exacerbated by the natural disasters in 2019, the insurgency in Northern Mozambique, escalating since 2017, and the global pandemic since 2020. Mozambique’s existing growth strategy has been limited in its capacity to generate productive jobs and support accelerated poverty reduction. However, the discovery of some of the largest natural gas (LNG) reserves in the world is expected to provide Mozambique with a transformative opportunity for sustained and inclusive growth. The Mozambique Country Economic Memorandum (CEM) assesses Mozambique’s current growth model and presents a set of recommendations to: (i) make the best use of the non-renewable natural resource revenues, which includes putting in place an adequate policy and institutional framework well ahead of the revenue windfalls from the LNG sector; and (ii) promote growth in non-extractive sectors, accompanied by spatial transformation, and improved agricultural productivity. The report consists of five chapters. Chapter one provides an overview of Mozambique’s current growth model, asking what’s driving growth and outlining why this model needs rethinking. Chapter two provides analysis of the potential impact of Mozambique’s resource boom on GDP, exports, revenue, and employment, and discusses how to make good use of the opportunities and manage the associated risks. Chapter three tells Mozambique’s growth story from a spatial perspective. It constructs a unique district-by-district sectoral GDP database to identify the main growth nodes in Mozambique and understand why there is a weak link between growth and poverty reduction. The services sector is the subject of chapter four, exploring how to overcome bottlenecks to deliver on its potential to drive growth in Mozambique. Chapter five continues this theme, examining the challenges posed to private sector growth by weak governance and rising corruption. All five chapters make policy recommendations for the way forward.